Assessing performance of container terminals: a colored Petri nets approach - Prata, Bruno de Athayde (2015)
This work reports a research which aims to propose a mathematical model, based on Discrete Events Theory, to assess performance of container terminals. Using colored Petri nets, the model has as the principal decision variable the goods transit time in the port area searching for the implications of that variable in the operational fleet size of transportation equipments. The model was applied to the case of the Port of Pecém. In the accomplished surveys, the logic of the system operations was described and data about the transport operational times in the terminal were gathered. Software CPNtools, editor and simulator of colored Petri nets, was used for the implementation, simulation and analysis of the proposed model. Analysis made possible to observe that the model works, in an acceptable way, as a reflection of the reality modeled but also that it requires some adjustments for a real-world better representation. Scenarios were analysed to evaluate the operational efficiency of the studied port in terms of containers flows to and from shipment. As conclusion, one can observe that the colored Petri nets are a feasible and useful technique for modeling, simulation and analysis of port terminal operations, mainly those related to container movements.